Pengaruh Minat Pendidikan Berwirausaha Menggunakan Sosial Media Terhadap Pebisnis Dikalangan Mahasiswa Universitas Pamulang - Yanti Haryantini (Thawalib: Jurnal Kependidikan Islam, 2021)
This study aims to determine the effect of interest in entrepreneurship using social media on business among students of the University of Pamulang.The object of this research is students who use social media as a medium for entrepreneurship at Pamulang University majoring in management. In the 2020 period with a population of 448. The number of samples taken with the Slovin formula in order to obtain a sample size of 84. The data in this study were processed by regression analysis to obtain the objectives of the study.The conclusion obtained in this study is that there is an influence of entrepreneurial interest in entrepreneurship on students. There is an influence of the use of social media on entrepreneurship in students.